Predicting passenger seat comfort and discomfort on the basis of human, context and seat characteristics: a literature review. Issue 7 (3rd July 2017) - Hiemstra-van Mastrigt, Suzanne; Groenesteijn, Liesbeth; Vink, Peter; Kuijt-Evers, Lottie F. M.
Abstract: This literature review focused on passenger seat comfort and discomfort in a human–product–context interaction. The relationships between anthropometric variables (human level), activities (context level), seat characteristics (product level) and the perception of comfort and discomfort were studied through mediating variables, such as body posture, movement and interface pressure. It is concluded that there are correlations between anthropometric variables and interface pressure variables, and that this relationship is affected by body posture. The results of studies on the correlation between pressure variables and passenger comfort and discomfort are not in line with each other. Only associations were found between the other variables (e.g. activities and seat characteristics). A conceptual model illustrates the results of the review, but relationships could not be quantified due to a lack of statistical evidence and large differences in research set-ups between the reviewed papers. Practitioner Summary: This literature review set out to quantify the relationships between human, context and seat characteristics, and comfort and discomfort experience of passenger seats, in order to build a predictive model that can support seat designers and purchasers to make informed decisions. However, statistical evidence is lacking from existing literature.